Vocational High School Strategic Efforts in Dealing with ASEAN Economic Communities - Suranto, Suranto; Rahmawati, Lutfi; Rohmah, Wafrotur; Gano-an, Jonathan Camana; Amanda, Bunga (Jurnal Paedagogy, 2023)
This study aims to reveal the readiness and efforts of vocational high schools in dealing with the ASEAN economic community. This research was qualitative research with an ethnographic design. Informants in this study were the principal, deputy head of the curriculum, the head of the accounting department, and the accounting teachers at SMK Negeri 1 Karanganyar and SMK Muhammadiyah 2 Surakarta. The data collection techniques used in this study were interviews and observation. Data analysis was carried out through data collection, data reduction, and data presentation to draw conclusions. The results of this study showed that SMKN 1 Karanganyar and SMK Muhammadiyah 2 Surakarta made preparatory efforts to deal with the ASEAN economic community. Those preparatory efforts included increasing the students’ skills through learning, both theoretically and practically, inside and outside the school environment, such as collaborating with the industrial and the business field, implementing the 2013 curriculum, increasing teacher knowledge through MGMP (Deliberation Subject Teachers), inviting teachers from institutions or universities, and completing school infrastructure. The research conducted in both schools revealed differences in efforts to prepare their students. These differences include SMK Negeri 1 Karanganyar innovating to invite other teachers to update the knowledge of teachers and students, build their accounting laboratories, and support teachers to be assessors. Meanwhile, SMK Muhammadiyah 2 Surakarta lacks school innovation and teachers as assessors. Furthermore, the laboratory of accounting majors is also used as other majors.